Studi Kuantitas dan Kualitas Biogas dari Berbagai Jenis Limbah Organik dan Waktu Fermentasi - Zahran William Dzulfiqar; Muhammad Miftahul Rizki; Ketut Sumada (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Biogas is a renewable energy obtained from the fermentation process or decomposition of organic materials by microorganisms in an environment without oxygen (anaerobic). This study aims to analyze the quantity and quality of biogas generated from various types of organic waste, including mustard greens, water spinach, cabbage, raja banana peels, and Medan orange peels, with fermentation periods of 10, 12, 14, 16, and 18 days. The quantity of biogas was measured based on the volume produced, while its quality was determined by the methane (CH₄) content using the Orsat Gas Analysis Apparatus. The results showed that raja banana peels produced the highest quantity and quality of biogas, with a maximum volume of 1393.2 ml and the highest methane content at 70.39% among all samples. These findings indicate that raja banana peels have significant potential as a substrate for biogas production. This research is expected to serve as a foundation for the development of technologies that utilize organic waste as an efficient, environmentally friendly, and sustainable alternative energy source.